Analisis Yuridis Terhadap Tindak Pidana Pemalsuan Akta Otentik oleh Notaris: Studi Kasus No. 146 K/PID/2015 - Suryanto, Jane Patricia (Universitas Ekasakti, 2024)
This discussion delves into the legal aspects of criminal prosecution concerning authentic deeds containing forged signatures, with a specific focus on the responsibilities of notaries in the creation of authentic deeds and the legal considerations by judges based on Supreme Court Decision Number 146K/PID/2015. The discourse encompasses the definition of forgery, the penalties that may be imposed on notaries, and the legal considerations regarding the authenticity of authentic deeds affected by forged signatures. Emphasis is placed on the evidence admissible in legal cases, the authority of officials creating authentic deeds, consistency with applicable laws, and potential legal consequences. Forgery within authentic deeds, including forged signatures, constitutes a serious criminal offense that can result in severe legal consequences for the perpetrators. The responsibility of notaries as officials responsible for creating authentic deeds is to ensure the validity and authenticity of such documents. Supreme Court Decision Number 146K/PID/2015 provides guidance on the considerations judges should take into account when assessing the authenticity of authentic deeds containing forged signatures, including handwriting expert opinions, the utilization of forensic technology, and an examination of the context surrounding the creation of the deed. The importance of consistency with applicable laws in the process of creating authentic deeds cannot be overstated, as it is a crucial factor in determining the validity of legal documents in court. Legal consequences that may arise from forged signatures within authentic deeds include the nullification of the deed, legal sanctions imposed on the perpetrators, and restitution for damages to the aggrieved parties.